Congruence and indifference between two molecular markers for understanding oral evolution in the Marynidae sensu lato (Ciliophora, Colpodea) - Dunthorn, Micah (Gustav Fischer Verlag, 2012)
Our understanding of the evolution of oral structures within the Colpodida is confounded by the low number of morphological characters that can be used in constructing hypotheses, and by the low taxon and character sampling in molecular phylogenetic analyses designed to assess these hypotheses. Here we increase character sampling by sequencing the mitochondrial SSU-rDNA locus for three isolates of the Marynidae sensu lato. We show that the inferred mitochondrial and nuclear SSU-rDNA trees, as well as concatenated and constrained analyses, are congruent in not recovering a monophyletic Marynidae. However, due to low node support, the trees are indifferent to whether the morphological characters used to unite the Marynidae are the result of retention of ancestral states or convergence. In light of this indifference and an increased amount of nuclear and mitochondrial SSU-rDNA data, alternative hypotheses of oral evolution in the Colpodida are presented.